ADSIG as Gen-Former providing three port network for soft coupling of distribution feeders in addition to wind energy harvesting. (May 2020) - Verma, Vishal; Singh, Ramesh; Gour, Ritika
Highlights: A concept of three (multiple) port network architecture involving Asymmetrical Dual Stator Induction Generator (ADSIG)mathematically analyzed to access the dependence of power routing on leading/lagging winding side (with respect to the rotor flux). The study has been conducted for operation of ADSIG in both generating as well as transformer mode of operation depending upon the wind speed. The performance of ADSIG has been demonstrated through experimentation, and results show effective coupling between the feeders with power injection and effective power distribution by ADSIG under perturbing load conditions on either of the connected feeders. The paper paves a way for the presence of multiple ADSIG units in future distribution feeders and designing reconfigurable distribution system with integrated wind energy systems. Abstract: With increase in the Electric Vehicle (EV) load the coupling of feeder in the distribution has become essential. The paper prescribes the use of multiple Asymmetrical Dual Stator Induction Generator (ADSIG) acting as 'Gen-Former' to draw out coupling of feeders for bidirectional power transfer in addition to energy harvesting from the feed on its rotor from wind energy source. The paper presents an analysis of soft coupling for two feeders by providing route for power to flow from one power feeder to other power feeder region in addition to harvesting power from wind energy turbine. Asymmetrical Dual Stator Induction Generator (ADSIG) is modeled and analyzed for enacting as soft coupler for power transaction between two feeders together with wind energy harnessing. An experimental study is also done on a scaled down 3.75 kW developed prototype in the laboratory. The performance of the proposed system is analyzed and results show effective coupling between the feeders with power injection and effective power distribution by ADSIG under perturbing load conditions on either of the connected feeders.